2019
DOI: 10.1016/j.redox.2019.101161
|View full text |Cite
|
Sign up to set email alerts
|

Short term Pm2.5 exposure caused a robust lung inflammation, vascular remodeling, and exacerbated transition from left ventricular failure to right ventricular hypertrophy

Abstract: Heart failure (HF) is the single largest cause for increased hospitalization after fine particulate matter (PM2.5) exposure. Patients with left HF often progress to right ventricular (RV) failure even with optimal medical care. An increase of PM2.5 of 10 μg per cubic meter was associated with a 76% increase in the risk of death from cardiovascular disease in 4 years' period. However, the role and mechanism of PM2.5 in HF progression are not known. Here we investigated the role of PM2.5 exposure in mice with ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
73
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 30 publications
5
73
2
Order By: Relevance
“…For example, He et al (9) have established that PM2.5 can cause inflammatory effects in MLE-12 cells, which are derived from a female mouse. In addition, multiple studies in male mice have reported that PM2.5 can activate inflammation and lead to lung injury (23)(24)(25). Altogether, these findings suggest that sex differences do not affect the outcome of PM2.5 exposure; therefore, the MLE-12 cell line was selected to perform this research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, He et al (9) have established that PM2.5 can cause inflammatory effects in MLE-12 cells, which are derived from a female mouse. In addition, multiple studies in male mice have reported that PM2.5 can activate inflammation and lead to lung injury (23)(24)(25). Altogether, these findings suggest that sex differences do not affect the outcome of PM2.5 exposure; therefore, the MLE-12 cell line was selected to perform this research.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient air pollution in both urban and suburban areas was estimated to cause 4.2 million premature deaths worldwide per year in 2016; this mortality is due to exposure to airborne particulates 2.5 µm or less in diameter (PM2.5), which cause respiratory and cardiovascular disease, and cancers [20]. Many epidemiological reports have linked exposure to air pollution and increased morbidity and mortality associated with cardiovascular and respiratory diseases, such as chronic obstructive pulmonary disease (COPD) and asthma [3,4,47]. Interestingly, although PM has been known to be a critical risk factor for COPD, evidence supporting the relationship between the incidence of COPD and PM2.5 is currently very limited and insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al (2020) found that C57BL/6 mice whole-body exposed to PM 2.5 (59.77 µg/m 3 ) sampled from Beijing, China exhibited severe lung injury and brosis [11]. They also demonstrated that treatment with local PM 2.5 polluted air at Beijing, China would strikingly induce lung oxidative stress and injury in mice for 3 weeks and 6 months, respectively [15,16]. Zhou et al (2019) exposed C57BL/6 mice to PM 2.5 collected from Shijiazhuang, China, and found that signi cant increase in circulating white blood cells and in ammation in lungs of mice from exposure groups [17].…”
Section: Introductionmentioning
confidence: 96%